Dynamics of participation in utilization of local value chain services: assessing barriers and enablers in Uganda - Emmanuel Bizimungu; Robert Sparrow; Ruerd Ruben; John Recha (Taylor & Francis group, 2026)
Integrating smallholders into agri-food value chains has become a widely endorsed strategy for transforming food systems and reducing poverty in agrarian communities. However, value chain development initiatives are increasingly criticized for their lack of inclusiveness—benefits tend to accrue to resource-rich households, while marginalized communities are often left behind, exacerbating social inequality. There is no clear consensus on the factors driving disparities in participation and utilization of value chain services. Using panel data from soybean smallholders in Uganda, we trace the evolution of participation in value chain service use. We employ a multinomial logit model to (a) identify the drivers and barriers to participation in value chain (VC) service utilization and (b) examine the determinants of variation in service uptake—specifically, the types and number of services used. While the Multinomial Logit Model is also used to analyse variation in service types, a Two-Part Model is applied to assess participation intensity. Our findings show that barriers such as insecure land tenure, limited education, poor access to credit, and distance from service points hinder inclusive participation. Value chain service delivery appears to operate as a mechanism for selecting more viable participants, suggesting that value chain service providers might be adopting risk-averse strategies that (whether intentionally or unintentionally) can exclude resource-poor households from accessing services. Moreover, exclusion tends to persist even after initial participation in farm-level training, limiting subsequent engagement with input and output market services. We discuss the implications of these findings for fostering more inclusive and resilient food systems.
Keywords: smallholder farmers; inclusive food systems; value chains; barriers; sustainability